Preparation of ingredients containing an ACE-inhibitory peptide by tryptic hydrolysis of whey protein concentrates - I. M. P. L. V. O. Ferreira (2007)
This study describes the characterisation of whey protein hydrolysates obtained from tryptic hydrolysis to assess their application as ingredients with angiotensin-converting-enzyme (ACE) inhibitory action. The levels of a-lactalbumin (alpha-la) and P-lactoglobulin (beta-lg) remaining after hydrolysis were quantified. Peptides were separated by RP-HPLC, and Ala-Leu-Pro-Met-His-Ile-Arg (ALPMHIR), the most potent beta-lg-derived ACE-inhibitory peptide was monitored. A correlation curve was established for the production of this peptide as a function of hydrolysis time. Heat-induced gelation of hydrolysates was studied by small-deformation rheology. The gelation times and the strength of the final gels were highly dependent on the degree of hydrolysis. Smaller peptides liberated by hydrolysis contributed to the inability of whey protein hydrolysates to gel. (c) 2006 Elsevier Ltd. All rights reserved.